Mathematical stimulation for bioelectrochemical behavior of a dualchambered microbial fuel cell (MFC) - Khazaal, Rusul M.; Ismail, Zainab Z. (Journal of Petroleum Research and Studies, 2020)
In this study, a steady-state bioelectrochemical model was developed to simulate the correlation between the acting overpotential and the produced current that is accounting for anode polarization. This study aimed to analyze the performance of a dual-chambered microbial fuel cell (MFC) equipped with two bio-anodes and fueled with real refinery oily sludge having a COD concentration of 13890 mg /L. Anode polarization data revealed a maximum current density of 6.07 A/m3 of the substrate at an overpotential of 1.83 V. In addition, the behavior of the experimental measurements revealed the dominance of the ohmic losses in the overall anode overpotential compared to activation and mass transfer losses, respectively. On the other hand, the suggested mathematical model was verified significantly by the obtained experimental data, achieving a determination coefficient (R2) of 0.96. Actual sustainable energy was also obtained using the reductive decrease of anode potential (RDAP) and it was found that the sustainable energy for this corresponding system can be attained when applying 17.6 KΩ as the external resistor.